2011
DOI: 10.2169/internalmedicine.50.4508
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Features of Acute-Onset Diffuse Interstitial Lung Diseases in Patients with Rheumatoid Arthritis Receiving Treatment with Biological Agents: Importance of <i>Pneumocystis</i> Pneumonia in Japan Revealed by a Multicenter Study

Abstract: Objective Acute-onset diffuse interstitial lung disease (AoDILD) in patients with rheumatoid arthritis (RA) has been a serious concern, especially for those under treatment with biological agents which may affect the presentation and outcome of AoDILD, including Pneumocystis pneumonia (PCP). Therefore, we conducted a retrospective, multi-center study of AoDILD in RA patients receiving biological agents. Methods Patients who developed AoDILD while receiving biological agents (infliximab, etanercept, adalimumab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 26 publications
0
42
0
3
Order By: Relevance
“…Therefore, we cannot completely exclude the possibility of false negative results in the remaining 66 cases. On the other hand, serum β-D-glucan is a reliable diagnostic marker for PJP (23)(24)(25). Because the sensitivity for PJP is very high, serum β-D-glucan can be used as a screening tool for PJP, especially for patients who are not suitable for the BAL procedure (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we cannot completely exclude the possibility of false negative results in the remaining 66 cases. On the other hand, serum β-D-glucan is a reliable diagnostic marker for PJP (23)(24)(25). Because the sensitivity for PJP is very high, serum β-D-glucan can be used as a screening tool for PJP, especially for patients who are not suitable for the BAL procedure (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, acute-onset diffuse ILD in patients with rheumatoid arthritis on treatment with biological agents is commonly due to Pneumocystis jirovecii infection [24]. The dilemma for the clinician is whether to increase or decrease the level of immunosuppression and institute intensive treatment for infection, tailored to cultured microorganisms.…”
Section: Acute Infectionmentioning
confidence: 99%
“…Some have documented that high A-aΔO 2 , combined bacteremia, elevated BUN, and preexisting lung disease are independent factors for a poor prognosis [21,22]. It has also been reported that early diagnosis and treatment initiation could lead to improved survival in non-HIV PCP [14,15,16,17,18,19,20,21,23,24]. Other studies evaluated by multivariate analyses that low serum albumin levels and mechanical ventilation are independent predictors of mortality [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of PCP was made according to the following criteria: (1) a positive PCR of P. jirovecii on samples of sputum or BAL fluid (BALF), (2) radiological findings on high-resolution chest computerized tomography (HRCT) such as unilateral or bilateral ground-grass opacity (GGO), and/or patchy consolidation, which are compatible with PCP [14,15,16], (3) compatible clinical symptoms including fever, cough, sputum, and dyspnea. Patients who had neither radiological findings nor clinical symptoms compatible with PCP, with a positive PCR of P. jirovecii but negative conventional staining (Grocott's stain or Diff-Quik), were considered as colonization cases and excluded from the study.…”
Section: Methodsmentioning
confidence: 99%